Source characteristics of the 2017 Mw6.4 Moijabana, Botswana earthquake, a rare lower-crustal event within an ancient zone of weakness - Materna, Kathryn (2021)
The 2017 Moijabana earthquake in central Botswana (Mw6.4) was a large and deep event for a continental interior and occurred in a region with little historical seismicity. Based on InSAR measurements of surface deformation spanning the event and teleseismic observations, we determine the ruptured fault plane and finite rupture model of the earthquake. Although this oblique normal-faulting earthquake is too deep to uniquely determine the rupture plane geometry from InSAR alone, the best-fitting fault plane constrained by the joint inversion of teleseismic waveforms and InSAR data has a southwest dip and a strike of 126°, roughly consistent with the geologically mapped strike of the Kaapvaal craton's northern edge. Our results indicate that the earthquake had a total duration of ∼10 s, characterized by two major asperities. The first asperity nucleated in the lower crust and then the rupture propagated up-dip. The lower crustal asperity shows a much shorter rise time compared with the shallower asperity, indicating that contrasts in stress or material properties may have played an important role in the rupture process. The earthquake appears to have occurred in the Limpopo belt, a Proterozoic orogenic belt that represents an ancient zone of weakness between the Archean Zimbabwe and Kaapvaal cratons. In the present day, this zone of weakness may be responding to the stress field imposed by the East African Rift System.